The secret of Castle Cant being an account of the remarkable adventures of Lucy Wickwright, maidservant and spy - Bath, K. P. (Kevin P.) (Little, Brown, 2006)
When twelve-toed orphan Lucy Wickwright is brought to Castle Cant to be serving girl to the Baron's daughter, the Adorable & Honorable Pauline, she becomes involved with revolutionaries and uncovers surprising palace intrigues.